The impact of artificial morality on the performance of textile industry of Asean Countries - Omar, Rusdi; Khamis, Kamarul Azman; Jermsittiparsertc, Kittisak; Kaliappen, Narentheren; Szymczyk, Katarzyna (Allied Academies, 2021)
The primary purpose of the article is to examine the artificial morality that is measured by the increase in machine output, increase in the accuracy of the machine, reduce the work hour of the labor and reduce the cost of output, impact on the performance of the textile industry in ASEAN countries. The data were gathered from the textile industry currently operating in the ASEAN countries from 2002 to 2018, and a fixed-effect model was employed to test the hypotheses of the paper but using STATA. The results uncovered a positive link between artificial morality and the textile industry's performance in ASEAN countries. These findings recommended to the policymakers and implementation authorities that they develop and implement the policies regarding improving the businesses' artificial morality that enhance the firm performance. Keywords: Artificial Morality, Firm Performance, Textile Industry, ASEAN Countries.